MEDICAL PERSONNEL’S LEGAL AWARENESS AS THE KEY OF PRINCIPAL QUALITY OF WORK WITH MINOR PATIENTS - Palkova, Karina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nowadays increasing attention is paid to the issues of the relationships between minor patients and medical personnel. There are several problematical issues in relationships mentioned above and one of the most significant is the legal regulation awareness of people providing medical services. The aim of the study is to make evaluation of the legal knowledge of medical personnel who work with minor patients and find out the main problems medical personnel deal with in particular area. Material and methods: the first group consisting of 70 medical personnel completed the questionnaire about knowledge of legal regulations by medical personnel. As the result the participants possess the low level of knowledge in providing information to minor patients about their health status. Insufficient knowledge is resulting in low quality of legal perspective of provided services. And this fact puts medical personnel at risk of being liable for breaching the laws.